2008
DOI: 10.1016/j.ijfoodmicro.2008.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Improving quantitative exposure assessment by considering genetic diversity of B. cereus in cooked, pasteurised and chilled foods

Abstract: The natural contamination of foods with a bacterial pathogen frequently consists of a mixture of strains with their own characteristics of survival, growth potential and virulence. Quantitative Microbial Risk Assessment (QMRA) must account for this genetic diversity to reflect the variability of the pathogen risk and to identify the genetic groups present at key stages of the food pathway. To describe the transmission dynamics of a heterogeneous population of B. cereus, we developed an exposure model that cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 32 publications
5
60
0
Order By: Relevance
“…Thus, B. cereus strains were activated at 7 o C, in agreement with published results (12,13), and resistance of B. cereus to low temperatures is not related to the disinfectant resistance of B. cereus. When B. cereus strains were subjected to 10 and 15 o C, strains treated with sodium hypochlorite (S-BC-50 and S-BC-52) had significantly (p<0.05) lower bacterial counts than other strains (data not shown).…”
Section: Resultssupporting
confidence: 90%
“…Thus, B. cereus strains were activated at 7 o C, in agreement with published results (12,13), and resistance of B. cereus to low temperatures is not related to the disinfectant resistance of B. cereus. When B. cereus strains were subjected to 10 and 15 o C, strains treated with sodium hypochlorite (S-BC-50 and S-BC-52) had significantly (p<0.05) lower bacterial counts than other strains (data not shown).…”
Section: Resultssupporting
confidence: 90%
“…Afterwards, these cultures were inoculated in Erlenmeyer flasks (250 ml) containing 50 ml fresh BHI broth and incubated at 30°C (Julabo SW22; Julabo Labortechnik, Germany) and at 12°C (Forma orbital shaker 481; Thermo Electron Corporation) with shaking at 200 rpm until the stationary growth phase. The latter temperature was chosen because various isolates of the B. cereus group were unable to grow at 10°C (1).…”
Section: Methodsmentioning
confidence: 99%
“…The strains were isolated from vegetable purees and semolina incriminated in the food poisoning cases. Together, they displayed phenotypic and genetic differences to other B. cereus Group strains (Afchain et al, 2008;Auger et al, 2008;Fagerlund et al, 2007;Rau et al, 2009) and a particular thermotolerant ecotype known as phylogenetic group VII (Guinebretière et al, 2008). Here, it is shown that these strains are closely related and represent a novel species of the B. cereus Group, for which the name Bacillus cytotoxicus sp.…”
Section: Introductionmentioning
confidence: 99%